Evaluation of host plant species for a trap cropping strategy in integrated pest management of pineapple mealybug (Dysmicoccus brevipes) - ABDULLAH, MOHAMMAD AZIZI; LATIP, NURUL FATIHAH ABD; MOHD HATTA, SITI KHAIRIYAH; YAAKOP, SALMAH; HAZMI, IZFA RIZA (The Indian Journal of Agricultural Sciences, 2024)
Pineapple mealybugs are responsible for the emergence of pineapple wilt disease and the subsequent transmission of the pineapple disease virus. This study aimed to evaluate the alternate host plants as potential trap crops for pineapple mealybug. A total of nine host plant species, banana, pumpkin, roselle, hibiscus, ground fig, okra, java grass, goose grass and rhodes grass were selected for the study. Thirty adult females of pineapple mealybug were reared on a pumpkin for two months. Three replicates of a plot (area covered with black netting measuring 3 m × 3 m) were set up. Nine host plant species, approximately 2–3 feet in a 16 inch × 16 inch polybag were arranged in a circle around the pumpkin. The effectiveness of the host plant species was determined by calculating the infestation of each plant species for six months (with two-week observations). Our findings revealed that the pineapple mealybug prefers banana with the greatest mean and SD value (621.7±172.7), followed by pumpkin (237.0±45.6) and the lowest one is rhodes grass (2.00±26.5). ANOVA results show that there is a significant difference between host plant species (F-value of 26.87 and a P-value < 0.00). The observations suggest that banana has the potential to be utilized as trap crops for pineapple mealybug, and can be considered in IPM strategy to control pineapple mealybug.